Case Marking in Tharu: A Comparative Perspective - Paudyal, Krishna Prasad; Khanal, Kamal Krishna (Nepalese Linguistics, 2023)
This paper compares the case marking system in Kathariya and Dangaura Tharu spoken by an ethnic group called Tharu. Both of these varieties typologically follow the nominative-accusative marking system. These varieties have different markers to code different cases. Only the Genitive marker -kə or -k are shared by both of these varieties. The dative-accusative markers -kehən, or -ke, instrumental marker -ləike, and ablative marker- ti are used in Kathariya Tharu. Dangaura Tharu is unique in its use of compound case marking in Genitive case. The locative marker in Kathariya Tharu is -me but it is -mə in Dangaura Tharu. The experiencer subjects in both of these varieties are dative case marked.